Gender disparities in COVID-19 vaccine hesitancy in high-income countries: an umbrella review protocol - Silvio Tafuri; Giuliano Piccoliori; Pasquale Stefanizzi; Adolf Engl; Christian J Wiedermann; Chiara Noviello; Claudia Palmieri (BMJ Open)
Introduction Vaccine hesitancy remains a critical public health challenge, especially in high-income countries. Gender differences in vaccine hesitancy can significantly affect vaccination rates and public health outcomes. The aim of this research is performing an umbrella review and meta-analysis to systematically investigate gender disparities in vaccine hesitancy for COVID-19 in high-income countries, as well as the quality, potential biases and dependability of epidemiological evidence.Methods and analysis The study will systematically search, extract and analyse data from reported systematic reviews and meta-analyses that focus specifically on gender differences in vaccine hesitancy. The search will include CINAHL, Cochrane Library, PubMed/MEDLINE, EMBASE and Epistemonikos for studies published from 2019 onward. The inclusion criteria will encompass systematic reviews and meta-analyses of non-interventional studies conducted in high-income countries. The identified factors contributing to vaccine hesitancy will be categorised based on demographic, psychological, social and economic dimensions. The methodological quality of the included meta-analyses will be assessed using the “Joanna Briggs Institute Critical Appraisal Checklist for Systematic Reviews and Research Syntheses” tool.Ethics and dissemination Ethical approval is not required for this umbrella review. These results will be published in a peer-reviewed journal.PROSPERO registration number CRD42024572978.